Students Workload and Stress Level during COVID-19 Pandemic - Nurwulan, Nurul Retno; Kurniawan, Bagus Aditya; Rahmasari, Dea Agatha; Rahmasanti, Jelita Widi; Abbas, Nur Aysah; Hadyanto, Muhamad Hirzi (Universitas Negeri Makassar, 2021)
The COVID-19 pandemic requires the change from learning activities in the classroom to online classes. While it is safer during the pandemic, it could result in a variety of issues, including the increase of studentsâ€™ stress levels. This study aimed to evaluate the effect of assignment workload on the stress level of college students. A total of 144 college students participated in the study. This study used quantitative research method with regression analysis as an approach to see the correlation between workload and stress levels in college students. The results showed that there is indeed a positive correlation between assignment workload and stress level. Additionally, we also found that gender significantly affected the stress level.Â Keywords: COVID-19, online classes, stress, assignment, workload.